Learning Management Innovation In Schools To Improve Student Achievement - Utamirohmahsari (JME Jurnal Management Education, 2025)
Innovations in learning management not only play a role in improving students' academic skills but also prepare them to face challenges outside the school environment. By utilizing digital technology and interactive learning methods, students can be more engaged and motivated in the teaching and learning process, which in turn improves learning outcomes. This study aims to explore the impact of student-focused learning innovations, the use of new technologies, and increasing community collaboration on learning. Some approaches, such as project-based learning and flipped classrooms, allow students to develop critical thinking skills, problem solving, and creativity, as well as develop social and emotional skills through collaborative learning. The use of technology also provides fluidity in the learning process and allows teachers to integrate student progress in real-time, so they can adjust the learning approach to individual needs. In addition, innovations in learning management also increase parental involvement in supporting students' academic and emotional development. These innovations overall contribute to the development of skills relevant to the demands of the world of work, such as communication, leadership, and teamwork, which prepare students to face global challenges in the future. This study suggests that educational institutions continue to adopt and develop innovative approaches that can prepare young people to remain competitive in a world full of change and new opportunities.